Dynamic Equilibrium of the Aurora A Kinase Activation Loop Revealed by Single‐Molecule Spectroscopy. Issue 38 (7th August 2017) - Gilburt, James A. H.; Sarkar, Hajrah; Sheldrake, Peter; Blagg, Julian; Ying, Liming; Dodson, Charlotte A.
Abstract: The conformation of the activation loop (T‐loop) of protein kinases underlies enzymatic activity and influences the binding of small‐molecule inhibitors. By using single‐molecule fluorescence spectroscopy, we have determined that phosphorylated Aurora A kinase is in dynamic equilibrium between a DFG‐in‐like active T‐loop conformation and a DFG‐out‐like inactive conformation, and have measured the rate constants of interconversion. Addition of the Aurora A activating protein TPX2 shifts the equilibrium towards an active T‐loop conformation whereas addition of the inhibitors MLN8054 and CD532 favors an inactive T‐loop. We show that Aurora A binds TPX2 and MLN8054 simultaneously and provide a new model for kinase conformational behavior. Our approach will enable conformation‐specific effects to be integrated into inhibitor discovery across the kinome, and we outline some immediate consequences for structure‐based drug discovery. Abstract : Dye quenching and single‐molecule fluorescence spectroscopy were used to monitor the conformation of the activation loop of Aurora A in solution. The position of the equilibrium between active and inactive conformations is changed by kinase ligands. Simple induced‐fit or conformational‐selection models do not explain the data. This has several consequences for drug design.